Is commercial/private sector access to administrative data inevitable? - Porteous, Carol (International Journal of Population Data Science, 2018)
Background Currently in the UK, access to publicly collected administrative data for use in research, is only available to accredited researchers. However, administrative data may be of interest to commercial or private sector organisations, some of whom have already controversially been partnering with universities and health researchers in the recent case of an NHS Trust partnering with Google Deep Mind. Objectives How do we deal with the issue of commercial/private sector access openly and critically as a society? Method This work will present the current landscape of commercial access to administrative data use and the results of a focus group with members of the public. Presented will be the views of the focus group in relation to different categories of commercial organisations and whether they should or should not be allowed access to administrative data and what conditions (if any) should be in place. Findings Initial findings indicate commercial access may be acceptable, but this raises new issues for society to consider about the role and extent of commercial/private sector reach.